Kualitas Pelayanan Service Express Agent di The ACC Resort Nusa Dua, Bali - Yanti, Ni Luh Putu Dewi Trisna; Rastitiati, Ni Kade Juli; Putra, Dewa Gede (Program Studi Manajemen Divisi Kamar, 2025)
This study aimed to find out the quality of Service Express Agent services at The ACC Resort, Nusa Dua, Bali. Data collection was conducted through direct interviews with the Service Express Manager, internal users, and external users at the resort. A qualitative descriptive data analysis was employed referring to the dimensions of service quality: tangibles (physical evidence), reliability, responsivenes, assurance and emphaty. The findings indicate that the overall sevice quality of the Service Express Agent is very good, particularly in the dimensions of tangibles, responsiveness, assurance and emphaty. However, there is a need for improvement in the reliability dimension, especially in addressing service delay during peak seasons or high-demand periods. To enhance service quality, ACC management should implement regular training and mentoring programs for staff.